2019
DOI: 10.1111/bph.14700
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Kv7 channel activity in human malignant hyperthermia syndrome unmasks a key role for H2S and persulfidation in skeletal muscle

Abstract: Background and Purpose Human malignant hyperthermia (MH) syndrome is induced by volatile anaesthetics and involves increased levels of cystathionine β‐synthase (CBS)‐derived H2S within skeletal muscle. This increase contributes to skeletal muscle hypercontractility. Kv7 channels, expressed in skeletal muscle, may be a molecular target for H2S. Here, we have investigated the role of Kv7 channels in MH. Experimental Approach Skeletal muscle biopsies were obtained from MH‐susceptible (MHS) and MH‐negative (MHN) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 62 publications
0
13
0
Order By: Relevance
“…H 2 S has also been demonstrated to relax vascular smooth muscle via the protein kinase G pathway as an endogenous inhibitor of phosphodiesterase and increases the levels of both cyclic GMP and cyclic AMP [ 48 , 49 ], as well as by activating Kv7 potassium channels [ 50 ]. Kv7 channels are also involved in CBS-derived H 2 S induced human malignant hyperthermia syndrome triggered by volatile inhalation anesthetics in skeletal muscle [ 51 ].…”
Section: Vascular Tone Regulation By H 2 S and H mentioning
confidence: 99%
“…H 2 S has also been demonstrated to relax vascular smooth muscle via the protein kinase G pathway as an endogenous inhibitor of phosphodiesterase and increases the levels of both cyclic GMP and cyclic AMP [ 48 , 49 ], as well as by activating Kv7 potassium channels [ 50 ]. Kv7 channels are also involved in CBS-derived H 2 S induced human malignant hyperthermia syndrome triggered by volatile inhalation anesthetics in skeletal muscle [ 51 ].…”
Section: Vascular Tone Regulation By H 2 S and H mentioning
confidence: 99%
“…In patch-clamp studies H 2 S gas 30 μM to 1 mM caused activation of K ATP channels in vascular smooth muscle from mesenteric arteries ( Tang et al, 2005 ), and 10 µM NaSH hyperpolarized mesenteric arteries by iberiotoxin-sensitive mechanism also suggesting the involvement BK Ca channels ( Jackson-Weaver et al, 2011 , 2013 ), and NaHS (1 mM) hyperpolarized rat aorta and directly activated K V 7 channels in CHO cells ( Martelli et al, 2013a ). Recent studies have also shown that direct activation of K V 7 channels by H 2 S donors protects against neuropathic pain ( Di Cesare Mannelli et al, 2017 ), and that direct persulfidation of K V 7 channels by H 2 S plays an important role in skeletal muscle hypercontractility in human malignant hyperthermia syndrome ( Vellecco et al, 2020 ). In agreement with studies in resistance arteries, in small mesenteric arteries contracted with the U46619, Na 2 S in the present study induced relaxations sensitive to high extracellular potassium and blockers of both ATP-sensitive, K V 7, and BK Ca channels suggesting involvement of these channels in Na 2 S relaxation, although electrophysiological measurements, e.g., membrane potential measurements or patch-clamp will be required to confirm the activation of K V 7 channels by Na 2 S in this preparation.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrogen sulfide (H 2 S) is considered an essential signaling molecule in the cardiovascular and nervous systems ( Szabó, 2007 ; Wallace et al, 2018 ) and a variety of pathophysiological changes including cancer, glycometabolic disorders, diabetes, sepsis, and human malignt hyperthermia are associated with altered endogenous levels of H 2 S ( Szabó, 2007 ; Szabo and Papapetropoulos, 2017 ; Vellecco et al, 2020 ). In the cardiovascular system, endogenous H 2 S can lead to both vasodilatation and vasoconstriction ( Li et al, 2015 ; Hedegaard et al, 2016 ; Gheibi et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…22 H 2 S induces the S-sulfhydration of Kv7 channel proteins and contributes to skeletal muscle hypercontractility in human malignant hyperthermia syndrome. 43 H 2 S protects diaphragm muscle fibrosis and strengthens diaphragmatic biomechanical properties in streptozotocin-induced diabetic rats. 44 H 2 S also alleviates the injury of skeletal muscle in ischemia-reperfusion rats, improves muscle functions in high-fat-diet-fed mice, and increases muscle mass in db/db diabetic mice.…”
Section: Introductionmentioning
confidence: 99%